2020
DOI: 10.1111/wvn.12470
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Incidence of Amiodarone‐related Phlebitis Through Utilization of Evidence‐based Practice

Abstract: Background: Intravenous (IV) amiodarone has multiple indications including treatment of hemodynamically unstable patients and the prevention of atrial or ventricular arrhythmias after thoracic surgery. Inflammation of the vein, or phlebitis, is the most common adverse event associated with peripherally administered amiodarone. In 2017, a rise in reported phlebitis incidents was occurring at one large academic medical center. Aim: This evidence-based quality improvement initiative aimed to decrease and enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, it has been found in clinical practice that although these methods can reduce the incidence of infection and promote patient recovery to a certain extent, the procedures are difficult with high requirements for nursing staff and slow effects. Moreover, these methods limit the patients' range of motion and reduce their nursing comfort [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been found in clinical practice that although these methods can reduce the incidence of infection and promote patient recovery to a certain extent, the procedures are difficult with high requirements for nursing staff and slow effects. Moreover, these methods limit the patients' range of motion and reduce their nursing comfort [12].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors of AIP include high drug concentration, longer infusion time, lower infusion rate, and higher total accumulative dose [7]. The current recommendation from several consensuses suggests the use of a lower concentration of amiodarone, application of the in-line filter, and using central venous infusion [10]. Studies reported that an amiodarone concentration of 1.2 mg/ml resulted in a significantly lower rate of phlebitis than an amiodarone concentration of 1.8 mg/ml [5,11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an integrated team approach with multidisciplinary healthcare providers for close monitoring of AIP development in amiodarone infusion cases, as well as hospital intravenous fluid team, were among the recommendation for AIP prevention [3,10]. However, these modalities are difficult to fulfill in some situations, for example, in an emergency setting where central venous catheterization is not suitable, and in fluid-restricted patients that could not tolerate the large volume of intravenous infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Compiling the data from these logs will provide a visual representation of work effort that would otherwise not be captured in the medical record. 13 Both methods provide a way to identify themes and extrapolate data reflective of an extended period. Team-level data can be presented by summarizing the data from the individual level portfolios or consultation logs and disseminated via infographics, annual reports, team-level portfolios, or other communication methods that elevate the visibility.…”
Section: Visualizing and Disseminating Valuementioning
confidence: 99%
“…Consultation logs can be used to track indirect (nonpatient) consultations with nurses or other healthcare team members over the course of a shift. Compiling the data from these logs will provide a visual representation of work effort that would otherwise not be captured in the medical record 13 . Both methods provide a way to identify themes and extrapolate data reflective of an extended period.…”
Section: Visualizing and Disseminating Valuementioning
confidence: 99%